Experimental scarcity increases the relative reinforcing value of food in food insecure adults. (1st September 2018) - Crandall, Amanda K.; Temple, Jennifer L.
Abstract: People with fewer financial resources are at greater risk for obesity, but the mechanisms of this relationship are not fully understood. One factor that is related, both cross-sectionally and prospectively, to obesity is the relative reinforcing value of food. It is possible that the experience of scarcity increases this reinforcing value. To date, no studies have examined this potential relationship experimentally in humans. The purpose of the studies presented here was to test the hypothesis that experimental manipulations of perceived scarcity would impact the relative reinforcing value of food. A secondary hypothesis was that individuals who report experiencing food insecurity would be more sensitive to these experimental manipulations. In order to test these hypotheses, we investigated the effects of experimentally manipulated scarcity on the relative reinforcing value of food in a laboratory setting. Study 1 had a within-subjects design and included 25 adults. Scarcity was manipulated by placing time and resource limits on the relative reinforcing value task and examining responding for a high calorie snack food versus that of an alternative reinforcer. Study 1 showed a tendency for food insecure participants to respond more for all reinforcers across conditions and have a higher proportional response for food when resources were limited. Study 2 also made use of a within-subjects design with 30 adults and primed scarcity by creating financial gains and losses on the Iowa Gambling Task. We observed higher relative reinforcing values of food among food insecure participants in the control condition, which decreased in the financial gain condition. When taken together, these two studies suggest that individuals who report experiencing food insecurity respond to acute manipulations of scarcity by increasing their reinforcing value of snack food.